Future Information Technology Tools for Fighting Substandard and Falsified Medicines in Low- and Middle-Income Countries - Rasheed, Huma; Höllein, Ludwig; Holzgrabe, Ulrike (Frontiers in Pharmacology, 2018)
Substandard and falsified medicines have emerged as a global public health issue within the last two decades especially in low- and middle-income countries. Serious consequences of this problem include a loss of trust and increased financial costs due to less disease control and more frequent complications during therapy. Of note, antimicrobial resistance is an additional long-term implication of poor-quality antimicrobials. This review covers information technology tools including medicines authentication tools as mobile apps and messaging service, 2D barcoding approaches with drug safety alert systems, web based drug safety alerts, radiofrequency identification tags, databases to support visual inspection, digital aids to enhance the performance of quality evaluation kits, reference libraries for identification of falsified and substandard medicine, and quality evaluation kits based on machine learning for field testing. While being easy to access and simple to use, these initiatives are gaining acceptance in low- and middle-income countries. Implementing 2D barcoding based on end-to-end verification and “Track and Trace” systems has emerged as a step towards global security in the supply chain. A breakthrough in web-based drug safety alert systems and data bases was the establishment of the Global Surveillance and Monitoring System by the World Health Organization in 2013. Future applications include concepts including “lab on a chip” and “paper analytical devices” and are claimed to be convenient and simple to use as well as affordable. The principles discussed herein are making profound impact in the fight against substandard and falsified medicines, offering cheap and accessible solutions.